Formulation of the Optimization Problem for Unit Commitment with Price Elasticity-Based Demand Response - Sijabat, Monika Leonita Srikarina; Fitri, Ismi Rosyiana (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
Integrating Demand Response (DR) programs into the Unit Commitment (UC) problem is a promising method to enhance the efficiency and reliability of power systems. This work introduces a new formulation that incorporates price elasticity into the UC problem using a relaxed optimization approach. Our objective is to maximize overall system performance by reducing generation costs and maximizing the utility function while accounting for how demand changes in response to electricity prices, i.e., price elasticity-based DR. The proposed model employs Mixed-Integer Linear Programming (MILP) techniques to efficiently solve the UC problem, using a linear function to model price elasticity-based DR. Our approach has demonstrated its effectiveness in achieving substantial cost reductions and improved load management, as shown through numerical simulations.